2021
DOI: 10.21926/obm.geriatr.2102167
|View full text |Cite
|
Sign up to set email alerts
|

Admiral Nurse Case Management within Enhanced Health in Care Homes

Abstract: The United Kingdom’s (UK) older population is higher than the global average. Over the next 20 years, England will see an increase in the number of older people who have higher levels of dependency, dementia, and comorbidity many of whom may require 24-hour care. Currently it is estimated that 70% of residents in nursing and residential care homes either have dementia on admission or develop it whilst residing in the care home. The provision of high-quality care for this population is a challenge with a lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Furthermore, as we have shown that caregiver voice is not always heard, there may be a role for independent advocacy. This may be afforded by Admiral Nurses whose triadic relationship‐centred approach facilitates shared decision‐making between the person with dementia, their family caregivers, and staff 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, as we have shown that caregiver voice is not always heard, there may be a role for independent advocacy. This may be afforded by Admiral Nurses whose triadic relationship‐centred approach facilitates shared decision‐making between the person with dementia, their family caregivers, and staff 33 …”
Section: Discussionmentioning
confidence: 99%
“…This may be afforded by Admiral Nurses whose triadic relationshipcentred approach facilitates shared decision-making between the person with dementia, their family caregivers, and staff. 33 Participants described an absence of follow-up care and single point of contact, as well as limited financial and social support. While observed in other studies, 8,21 our analyses offer new insights by suggesting this is driven by a systemic lack of parity of esteem between dementia and other life-limiting illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, evidence of the cost-saving implications of an Admiral Nurse model is also starting to emerge. For example, a small pilot study [40] found that the Norfolk Admiral Nurse service meant a saving to the health and social care economy of GBP 426,601, hence demonstrating that it is possible to deliver gold-standard clinical care with no financial risk to the taxpayer. However, despite dementia being the leading cause of death among people in the UK, there are currently only 376 Admiral Nurses and only a very small proportion of these are available as formal support for families affected by YOD, which are more likely to have younger members [41].…”
Section: Discussionmentioning
confidence: 99%